KOMPARASI KINERJA OBLIGASI SYARIAH IJARAH DAN OBLIGASI KONVESIONAL PERIODE 2007–2010 Indah Yuliana Dewi Rahmawati Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang Jalan Gajayana 50 Malang Abstract In determining investment decisions - Yuliana, Indah; Rahmawati, Dewi (El Dinar: Jurnal Keuangan dan Perbankan Syariah, 2013)
In determining investment decisions concerning the future which is definitely or uncertain, investors are not only required to have special skills or sharpening intuition alone to face risks of the investment made. Investors should also determine the performance of the two obligations, which are more profitable to invest. These goals of study are to look at differences in the performance of Conventional and Syari’a Ijara Obligation based on nominal yield, yield to maturity, current yield and realized yield. Test conducted in this study uses an independent model analysis of t-test samples. Before testing, the initial step is to perform calculations based on the performance of the nominal yield, yield to maturity, current yield and realized yield. The result of study on statistical analysis are using independent t-test sample with significant level of 5% based on nominal variable yield, yield to maturity, current yield and realized yield. That the nominal variable yield, yield to maturity and current yield show not significant performance difference between Conventional and Syari’a Ijara Obligation. Ijara Obligation provides the average amount of fee for an investment amounting to 48.86% in 2007–2010. While Conventional Obligation can only the coupon rate of 44.99%. The yield to maturity on average Syari’a Ijara Obligation to 46.92%. From the position of current yield, which is a comparison of fees at market price. Syari’a Ijara Obligation has the highest current yield better than Conventional Obligation. Although the realized yield on the variables, Syari’a Ijara Obligation are still not be able to provide better value than the fee a Conventional Obligation. Keywords: performance, ijarah islamic obligation, conventional obligation, independent sample t-test.